The kinetochore as a target for the development of mitosis specific anti-cancer drugs - Yen, Tim (Henry Stewart Talks, 2009)
Mitosis is critical for cells to proliferate and is a major target of current anti-cancer drugs such as paclitaxel and vinca alkaloids, Characterization of proteins essential for mitosis has made available the opportunity to develop new anti-mitotic agents, Expanding the number of anti-cancer drug targets should significantly improve the response of tumors to chemotherapies